Pengaruh Persediaan Bahan Baku Terhadap Kualitas Produk di CV. Lenta Desa Dahana Kecamatan Bawolato Kabupaten Nias - Paulus Hengki S. Zebua; Jeliswan B.I.J. Gea; Otanius Laia; Eduar Baene (Departement of Mathematics Education, 2024)
Raw material inventory is a key element in the manufacturing process that has a significant influence on product quality. Efficient and effective management of raw materials is essential in ensuring the final product meets established quality standards. There are also things that are unsatisfactory on the CV. Lenta experienced several obstacles, such as the quality of the products produced still not reaching what customers expected, this was due to limited supplies of raw materials and also less than optimal production processes. Research Objectives: (1) To find out whether there is an influence of raw material supply on product quality; (2) Knowing how much influence raw material supplies have on product quality. The type of research used in this research is quantitative research. Research results: (1) Raw Material Supplies have a positive effect on Product Quality. This is justified by the value of valid data processing results. Variables (2) The results of the t test for variables X and Y processed in this research Ha are accepted and Ho is rejected, meaning that there is a significant influence of variable X on variable Y on CV. Lenta